The Osteogenesis Mechanisms of Dental Alveolar Bone Socket Post Induction with Hydroxyapatite Bovine Tooth Graft: An Animal Experimental in Rattus norvegicus Strain Wistar - Zubaidah, Nanik; Pratiwi, Dian Dwi; Masa, Maria Margaretha S. Nogo; Setiawatie, Ernie Maduratna; Kunarti, Sri (European Journal of Dentistry, 2022)
Objectives Surgical endodontics (hemisection) commonly involves the alveolar bone socket and the periradicular tissue. In today's era, optimizing the bone healing process is updated by using bone graft induction. This study explores the mechanisms of bone healing of the alveolar bone socket post-dental extraction of Wistar rats after administration of a bovine tooth graft (hydroxyapatite bovine tooth graft [HAp-BTG]).Materials and Methods Fifty Wistar rats were randomly selected into two groups, control and treatment, and into five subgroups on days 3, 7, 14, 21, and 28. The postextraction socket was filled with polyethylene glycol (PEG) as the control and PEG + HAp-BTG as the treatment group. On days 3, 7, 14, 21, and 28, Wistar rats were sacrificed, mandibles were taken, paraffin blocks were made, cut 4 µm thick, and made into glass preparations for microscopic examination. The variable analysis was performed by staining hematoxylin-eosin for osteoblasts (OBs) and osteoclasts (OCs) and immunohistochemistry for runt-related transcription factor 2 (RUNX2), osterix (OSX), osteocalcin (OCN), bone morphogenic protein (BMP) 2. We analyzed the expressed cell count per microscope field.Results In general, the number of cell expressions in the treatment group was significantly higher and faster, except for significantly lower OC. The high variables peak occurred on day 14 for RUNX2 and OCN, on day 7 for OSX, while OB significantly increased on day 21 and remained until day 28. The decrease of OC cells occurred on day 7 and remained low until 28 days. BMP2 was first dominantly induced by HAp-BTG, then the others.Conclusion HAp-BTG can induce higher and faster bone healing biomarkers. BMP2 is the dominant first impacted. On the 28th day, it did not significantly express the suppression of OC by OB, which entered the bone formation and remodeling step.
Keywords: hydroxyapatite bovine tooth graft; osteogenesis; osteoblast; osteoclast; dental health